Affective Realities and Conceptual Contradictions of Patricia Piccinini’s Art: Ecofeminist and Disability Studies Perspectives - Lorek-Jezińska, Edyta (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The recent exhibition of Patricia Piccinini’s art called That’s Us (Toruń, CSW) largely represents the Australian artist’s visions and fascinations known from earlier exhibitions. Questioning and erasing the borders between species, the affective realities of Piccinini’s art are bound to the concepts of care, empathy and fragility, which refigure what is human and non-human and the relations between them by expanding the notion of mothering and fostering to include interspecies relations. Beginning with a discussion of the uncanny, abjection and monstrosity, this article aims to examine the complicated implications of interpreting Piccinini’s art within the conceptual framework of ecofeminism, as well as in the context of disability aesthetics. In her explorations of different and alternative corporealities, Piccinini, among many other things, asks questions about ideologies of normativity and able-bodiedness, suggesting the possibility of going beyond them.